Symposium on Environmental Chemistry for Securing Water Quality - Dawlatana, Mamtaz (Bangladesh Journal of Scientific and Industrial Research, 2017)
This Special Issue contains the abstracts from the "Symposium on Environmental Chemistry for Securing Water Quality" which was held on 30th July 2017 at the Bangladesh Council of Scientific and Industrial Research (BCSIR), Dr. Qudrat-I-Khuda Road, Dhanmondi, Dhaka-1205, Bangladesh. Organised by the Bangladesh Journal of Scientific and Industrial Research (BJSIR). Bangladesh J. Sci. Ind. Res. 52 (Special Issue), 1-63, 2017